2011
DOI: 10.1186/1471-2148-11-45
|View full text |Cite
|
Sign up to set email alerts
|

The origin of multicellularity in cyanobacteria

Abstract: BackgroundCyanobacteria are one of the oldest and morphologically most diverse prokaryotic phyla on our planet. The early development of an oxygen-containing atmosphere approximately 2.45 - 2.22 billion years ago is attributed to the photosynthetic activity of cyanobacteria. Furthermore, they are one of the few prokaryotic phyla where multicellularity has evolved. Understanding when and how multicellularity evolved in these ancient organisms would provide fundamental information on the early history of life an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
205
2
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(233 citation statements)
references
References 109 publications
16
205
2
3
Order By: Relevance
“…19, 21, and 24). This rooting, however, is sensitive to the choice of out-group species (25). In contrast to these results, we find Gloeobacter violaceus emerging relatively late (node 16 in Fig.…”
contrasting
confidence: 55%
“…19, 21, and 24). This rooting, however, is sensitive to the choice of out-group species (25). In contrast to these results, we find Gloeobacter violaceus emerging relatively late (node 16 in Fig.…”
contrasting
confidence: 55%
“…15) gave rise to chloroplasts. However, this classification is mainly based on morphology, and recent phylogenetic studies 12 have shown that morphological characters are poor indicators of relatedness in cyanobacteria. Hence, doubt still remains concerning the exact origin of chloroplasts, and the release of more cyanobacterial genome sequences may alter our understanding of the origin of the Toc75 and OEP80 families.…”
Section: Phylogenetic Analysis Of Toc75 and Oep80 Proteinsmentioning
confidence: 99%
“…To root our tree, we used a sequence from Gloeobacter violaceus, which is hypothesized to form the sister group of all other cyanobacteria. 12,13 Doing this (in addition to an extensive reciprocal search for homologs among cyanobacterial sequences) showed that all eukaryotic representatives of the Toc75 and OEP80 clades probably have a single common origin in prokaryotes. Uncertainty in this regard largely derives from a lack of information on the identity of the cyanobacterial group from which chloroplasts originate.…”
Section: Phylogenetic Analysis Of Toc75 and Oep80 Proteinsmentioning
confidence: 99%
“…Numbers at the nodes represent the posterior probability. The grouping of cyanobacteria is according to Schirrmeister et al, 2011. Cyanobacteria marked with an asterisk (Gloeobacter violaceus PCC 7421 and Cyanobacterium UCYN-A) are devoid of the Rps1b homolog.…”
Section: High Incidence Of Short Cis-encoded Asrnasmentioning
confidence: 99%